PREVENÇÃO DE INFECÇÕES SEXUALMENTE TRANSMISSÍVEIS NO CONTEXTO UNIVERSITÁRIO - Pimentel, Angela Maria de Souza (2020)
The accelerated growth of diseases transmitted through sexual intercourse has challenged health systems around the world, as they represent a serious public health problem. There has been a considerable increase in cases of such diseases among young peopl